2006
DOI: 10.1177/0961203306069352
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic value of autoantibodies in Puerto Ricans with systemic lupus erythematosus

Abstract: The aim of this study was to determine the association between lupus autoantibodies and the clinical manifestations and outcome in a cohort of Puerto Ricans patients with systemic lupus erythematosus (SLE). All patients fulfilled the American College of Rheumatology classification criteria for SLE. Demographic parameters, clinical manifestations over time and damage accrual were obtained at the last study visit. Disease damage was assessed with the Systemic Lupus International Collaborating Clinics Damage Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
25
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 39 publications
(59 reference statements)
8
25
1
2
Order By: Relevance
“…Associations between autoantibodies and renal involvement have been extensively studied; however, only the relationship between anti-dsDNA antibodies and lupus nephritis has been consistently established [2, 4, 13]. We found that anti-Sm antibodies were significantly associated with renal involvement.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Associations between autoantibodies and renal involvement have been extensively studied; however, only the relationship between anti-dsDNA antibodies and lupus nephritis has been consistently established [2, 4, 13]. We found that anti-Sm antibodies were significantly associated with renal involvement.…”
Section: Discussionmentioning
confidence: 62%
“…Previous data regarding this association have been inconsistent [410, 1217, 23, 24, 2734]. A prospective cohort study of 201 Puerto Rican patients showed associations of anti-Sm antibodies with proteinuria, hematuria, urinary cellular casts, nephrotic syndrome, renal insufficiency, and end-stage renal disease [4]. Also, in a case-control study, Alba et al found that anti-Sm antibodies were linked with biopsy-proven lupus nephritis [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Así, la población blanca que vive en los Estados unidos o en el Reino Unido parece tener un mejor pronóstico que la población asiática que ha emigrado a estos países. Estudios recientes realizados en América Latina en pacientes adultos con LES mostraron que la población mestiza multiétnica presentó casos más severos que los pacientes de origen Europeo puro [4].Aunque la etiología y mecanismo patogénico del LES no ha sido claramente elucidado se acepta que es una patología multifactorial, resultante de la interacción compleja de factores genéticos y ambientales [5]. Se caracteriza por la producción de autoanticuerpos y la formación y depósito de complejos inmunes.…”
unclassified
“…En Colombia, a diferencia de otros países, los pacientes con LES mueren principalmente por las complicaciones de tipo renal [4]. Por tanto, es muy importante además de los autoanticuerpos mencionados, la determinación de otros que también contribuyen a la lesión glomerular.…”
unclassified